KUPAS TUNTAS PERAN DIGITALISASI PERPAJAKAN - Farras Mufidah, Imtiyaz; Anisaul Hasanah (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
This research focuses on thoroughly examining the modernization of taxation with all-electronic tax applications. The era of taxation digitalization has affected taxpayer services to fulfill their tax obligations to be easier, faster and more accurate. This study uses a qualitative method with a comprehensive and thorough Focused Discussion Group (FDG) technique. The participants in this study were FEB students at Universitas Selamat Sri. Based on the results of the study, it shows the important role of taxes, namely, tax digitalization in Indonesia's development which must continue. Students as the younger generation or Gen-Z have an important role in the development and progress of Indonesia. The role of higher education institutions is also very important as the prime mover for creating tax awareness, both in tax digitization such as e-registration, e-SPT, e-Faktur, e-Form, e-Billing, and e-Filling